2003
DOI: 10.1042/bj20030887
|View full text |Cite
|
Sign up to set email alerts
|

Processing of N-linked glycans during endoplasmic-reticulum-associated degradation of a short-lived variant of ribophorin I

Abstract: Recently, the role of N-linked glycans in the process of ERAD (endoplasmic reticulum-associated degradation) of proteins has been widely recognized. In the present study, we attempted to delineate further the sequence of events leading from a fully glycosylated soluble protein to its deglycosylated form. Degradation intermediates of a truncated form of ribophorin I, namely RI(332), which contains a single N-linked oligosaccharide and is a substrate for the ERAD/ubiquitin-proteasome pathway, were characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 54 publications
(114 reference statements)
3
34
0
Order By: Relevance
“…An increasing number of reports suggest that the N-glycanase is located in or on ER membrane because, in the presence of proteasome inhibitors, the glycosylated protein and deglycosylated intermediates are either exclusively or predominantly associated with the ER rather than with the cytosol (39). This model is supported by various studies using diverse glycoproteins as substrates, e.g., Ig subunits (40), class I MHC heavy chains (41) a ribophorin-I variant (42), cog thyroglobulin mutant (1), cystic fibrosis transmembrane regulator (43), and T cell receptor ␣-subunit (44). These findings also suggests that N-deglycosylation and proteasome-mediated degradation of proteins may be coupled events.…”
Section: Discussionmentioning
confidence: 96%
“…An increasing number of reports suggest that the N-glycanase is located in or on ER membrane because, in the presence of proteasome inhibitors, the glycosylated protein and deglycosylated intermediates are either exclusively or predominantly associated with the ER rather than with the cytosol (39). This model is supported by various studies using diverse glycoproteins as substrates, e.g., Ig subunits (40), class I MHC heavy chains (41) a ribophorin-I variant (42), cog thyroglobulin mutant (1), cystic fibrosis transmembrane regulator (43), and T cell receptor ␣-subunit (44). These findings also suggests that N-deglycosylation and proteasome-mediated degradation of proteins may be coupled events.…”
Section: Discussionmentioning
confidence: 96%
“…The normal function of ERAD is to transport misfolded proteins (marked by ubiquitination) from the ER back to the cytosol for proteosomal degradation; it seems possible that, like MMTV Rem, JSRV P70 env could be transported back to the cytoplasm by this mechanism without degradation. In mammalian cells, misfolded proteins are targeted to the ERAD pathway following the removal of 3 to 4 mannose residues by ER processing alpha 1,2-mannosidase (ER ManI) (58)(59)(60)(61). P70 env could be a misfolded version of Env (or at least appears to be misfolded to the ERAD machinery) that becomes more abundant in cells that are cotransfected with Zfp111.…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting evidence also suggested localization in the ER lumen (Weng and Spiro, 1997). PNGase in higher eukaryotes acts on a diverse range of misfolded glycoprotein substrates, namely immunoglobulin (Ig) subunits (Mancini et al, 2000), MHC class I heavy chains (Kamhi-Nesher et al, 2001), a ribophorin I variant (Kitzmuller et al, 2003), cog thyroglobulin mutant (Tokunaga et al, 2000), cystic fibrosis transmembrane regulator (Xiong et al, 1999), and T-cell receptor (TCR) ␣-subunits (Yu et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…PNGase has been reported to localize in the cytosol (Suzuki et al, 1998) (Suzuki et al, 1997), and the lumen of the ER (Weng and Spiro, 1997). Previous studies showed that glycosylated proteins or deglycosylated intermediates are predominantly associated with the microsomes rather than with the cytosol (Kitzmuller et al, 2003). The observation that PNGase is found in the cytosol and associated with the ER (Katiyar et al, 2004) can be explained by the presence of alternative ERAD routes, with deglycosylation either coupled to or independent of retrotranslocation (Misaghi et al, 2004).…”
Section: Introductionmentioning
confidence: 96%